The background of board, compensation, leverage, and fixed asset revaluation decision - Fanani, Zaenal; Kamelia, Arika (Jurnal Keuangan dan Perbankan, 2020)
This research aims to obtain empirical evidence in Indonesia whether it is true that companies with boards of commissioners and directors with political, accounting, military background, and the amount of compensation received will affect the selection of revaluation methods to measure their fixed assets that revaluation is commonly used to facilitate the company in obtaining additional loan funds and attract investors to invest. This can occur because in the revaluation method, the company's fixed assets are presented under fair conditions. In addition, this study also wants to test whether a company with high debt levels will tend to revalue its fixed assets measured by the leverage of the company. This research used the entire company population in all types of industries listed on the IDX for the period 2016. The final sample used in this research was 458 using logistic regression analysis. In this research, it is found that political background and accounting background has no positive effect, military background had positive effect, and compensation and leverage had no negative effect on the asset revaluation decision remains. JEL Classification: M48, D72, G32DOI: https://doi.org/10.26905/jkdp.v24i3.4220